Hubungan Kecemasan dengan Pola Tidur Lansia Hipertensi dan Tidak Hipertensi - Try Nurhayati; Latifa Aini Susumaningrum; Hanny Rasni; Tantut Susanto; Diana Kholida (Jurnal Keperawatan, 2020)
Elderly with hypertension have a higher of anxiety. Mental condition influence sleep patterns of elderly. The purpose of this study was to analyze the differenced anxiety and sleep patterns among elderly with hypertension and non-hypertension in nursing home (UPT PSTW) of Banyuwangi. A case-control design was used among 51 elderly (18 of control groups and 33 of case groups) using purposive sampling. A Geriatric Anxiety Inventory questionnaire was used to measure anxiety score of elderly, while Pittsburgh Sleep Quality Index questionnaire was used to measure sleep pattern. Chi-square test was used to analyze relationship between anxiety and sleep patterns among elderly with hypertension and non-hypertension. The results showed there were 57.6% of elderly with systolic hypertension having anxiety and 75.8% of elderly with systolic hypertension having poor sleep patterns. There were significantly differenced anxiety and sleep patterns between control and case groups (p<0,05). However, level of anxiety and level of sleep pattern were more higher in case group compare to control groups (p<0,05). The conclusion of this study, there is differenced anxiety and sleep patterns among elderly with hypertension and non hypertension. Therefore, elderly should more adaptive for mentainance of stressor and avoiding anxiety to reduce sleep disorder.